The Application of a System of Eye Tracking in Laparoscopic Surgery: A New Didactic Tool to Visual Instructions - Marín-Conesa, Ester; Sánchez-Ferrer, Francisco; Grima-Murcia, María Dolores; Sánchez-Ferrer, María Luisa (Frontiers in Surgery, 2021)
Introduction Laparoscopic surgery is an increasingly used technique, but it requires a high degree of learning and the communication between the operating room crew is considerably difficult. The use of eye tracking has been proposed as a didactic and evaluation tool in several settings, including in laparoscopy in simulators. Objectives This study aimed to evaluate the usefulness of the use of eye tracking systems (Tobii glasses 2) in laparoscopic surgery as a didactic and assessment tool to improve communication in the operating room and improving security´s patient. Methodology An anonymous survey was sent to the Students and medical teachers of a Faculty of Medicine and practicing doctors and residents. The message contained an explanation about the use of the Tobii glasses, a link to watch the video showing its use in a laparoscopic surgery and the survey to complete after watching the video. Results The survey was answered by 113 participants (51.3% medical students, 27.4% medical teachers, 18.6% practicing doctors and 2.7% medicine residents). 83% agreed with the usefulness of the "Tobii glasses" in the operating room for improving communication between the main surgeon and the assistant, for learning complex surgeries techniques, for obtaining didactic videos and for indicating anatomical structures. The item worse scored was the glasses price. Conclusions It is possible to record and project expert gaze pattern in the operating room in real time using Tobii glasses. This device allows to improve communication among surgical crew and learning of residents improving the security of the surgical patient.